A Hierarchical Fuzzy Control Design for Indoor Mobile Robot. (5th March 2014) - Abdessemed, Foudil; Faisal, Mohammed; Emmadeddine, Muhammed; Hedjar, Ramdane; Al-Mutib, Khalid; Alsulaiman, Mansour; Mathkour, Hassan
This paper presents a motion control for an autonomous robot navigation using fuzzy logic motion control and stereo vision based path-planning module. This requires the capability to maneuver in a complex unknown environment. The mobile robot uses intuitive fuzzy rules and is expected to reach a specific target or follow a prespecified trajectory while moving among unforeseen obstacles. The robot's mission depends on the choice of the task. In this paper, behavioral-based control architecture is adopted, and each local navigational task is analyzed in terms of primitive behaviors. Our approach is systematic and original in the sense that some of the fuzzy rules are not triggered in face of critical situations for which the stereo vision camera can intervene to unblock the mobile robot.